Medical nutritional therapy during pharmacotherapy for obesity: expert insights - Matylda Kręgielska-Narożna; Katarzyna Pastusiak-Zgolińska; Lucyna Ostrowska; Paweł Bogdański (Studia Medyczne)
This manuscript provides a comprehensive overview of expert experiences and perspectives on the role of medical nutrition therapy in enhancing the outcomes of pharmacotherapy for obesity. Through a detailed examination of current practices, challenges, and future directions, this paper seeks to contribute to developing integrated treatment strategies that maximise health benefits for patients with obesity. The findings underscore the importance of a multifaceted approach that includes nutrition, physical activity, and psychological support provided by an interdisciplinary team. Future guidelines should incorporate these comprehensive strategies to improve obesity management effectively.